REVIEW π: WHAT IS THE DESCRIPTION OF STUDENTS' INTEREST IN PHYSICS? - Agus Budiyono; Linda Tri Antika (JURNAL PENA SAINS, 2018)
This study was based on the potential of new methods in knowing students' interest in physics lessons. Interest in learning physics was the tendency and interest of students to learn the process and try to know and understand the material physics with experience of the environment both content and contextual. The subject of physics was more emphasis on the count, and then in each calculation equation was made in the form of symbols. Symbols that are often used in physics are the Greek alphabet. One of the most commonly used was the symbol "π." It was a Greek alphabet pronounced with pi. It was commonly used on specific subjects. The value "π" was 3.14 or 22/7 otherwise the value "π" was 180°. The use of "π" symbol in the level of education unit of High School as much as ten material of physics.